Hyperpartisan News Use: Relationships with Partisanship and Cognitive and Affective Involvement. Issue 2 (4th March 2021) - Peacock, Cynthia; Hoewe, Jennifer; Panek, Elliot; Willis, G. Paul
ABSTRACT: This paper revisits the issue of partisan selectivity in the era of prevalent false, misleading, and biased information. We surveyed a representative sample of adults living in the United States to investigate the relationships among hyperpartisan news use, partisanship, and cognitive and affective involvement. First, we find that strong partisanship—from both Democrats and Republicans—relates to exposure to both left- and right-leaning hyperpartisan news. Second, exposure to left-leaning hyperpartisan content relates to negative affective involvement, while exposure to right-leaning hyperpartisan news relates to positive affective involvement. Neither left- nor right-leaning hyperpartisan news use relates to cognitive involvement, though traditional news use does. These findings add to the literature on partisan selective exposure and provide new details about the makeup of news audiences and their cognitive and affective involvement with hyperpartisan news.